Getting started with Simulink : get up and running with Simulink with this hands-on, easy to read guide - Zamboni, Luca (Packt Publishing, 2013)
This practical and easy-to-understand learning tutorial is one big exciting exercise for students and engineers that are always short on their schedules and want to regain some lost time with the help of Simulink. This book is aimed at students and engineers who need a quick start with Simulink. Though it's not required in order to understand how Simulink works, knowledge of physics will help the reader to understand the exercises described.